Interplay between flaviviruses and the interferon response: mechanisms of immune evasion and therapeutic implications - Han, Jiayin; Yin, Yue; Yuan, Jing (Frontiers in Pharmacology, 2026)
The genus Orthoflavivirus encompasses a group of medically significant arthropod-borne viruses, such as dengue virus (DENV), Japanese encephalitis virus West Nile virus Zika virus (ZIKV), and others, which pose persistent global public health threats. The host interferon (IFN) system constitutes a pivotal first line of defense against these viral infections. However, orthoflaviviruses have evolved a remarkable array of sophisticated strategies to antagonize both the induction and signaling pathways of type I and III IFNs. This review systematically summarizes the mechanisms by which orthoflaviviruses evade the IFN response, primarily by employing viral proteins to target key host factors in pattern recognition receptor signaling pathways (e.g., RIG-I, MDA5, MAVS, TBK1, STING, IRF3) and the JAK-STAT signaling cascade (e.g., STAT1, STAT2, IFNAR1). Furthermore, we highlight the critical and complex roles of IFNs at the placental and blood-brain barriers (BBB), the primary sites for transplacental transmission and neuroinvasion. At these barriers, IFNs play a dual role: they exert essential antiviral effects to restrict viral replication, but may also contribute to immunopathology. The delicate balance of IFN responses determines the outcomes of congenital infection and neurological diseases. Finally, we discuss the therapeutic potential of harnessing the IFN pathway, while also acknowledging the challenges and need for further in vivo studies to translate these insights into effective treatments for flavivirus-associated diseases.